Nepal pilots smart tools to transform its irrigation water management - Nepal, Santosh; KC, Jibesh; Khanal, Anup; Bhatt, Dinesh (International Water Management Institute, 2025)
The Babai irrigation project in western Nepal is using real-time data and soil sensors to address irrigation inequality and enhance farm productivity, while offering a scalable model for an evidence-based irrigation system across the country.